2019
DOI: 10.1371/journal.pgen.1007934
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study reveals a novel regulator of ovule number and fertility in Arabidopsis thaliana

Abstract: Ovules contain the female gametophytes which are fertilized during pollination to initiate seed development. Thus, the number of ovules that are produced during flower development is an important determinant of seed crop yield and plant fitness. Mutants with pleiotropic effects on development often alter the number of ovules, but specific regulators of ovule number have been difficult to identify in traditional mutant screens. We used natural variation in Arabidopsis accessions to identify new genes involved i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 59 publications
3
34
0
Order By: Relevance
“…Overexpression of genes regulating fertility and seed set does not increase SNS because they do not enhance the ovule initiation and ovule number. Although GWAS analysis of ovule number identified NERD, which positively regulates ovule number and SNS, it still regulated ovule number through helping ovule development and fertility [60]. However, only a few genes were reported to positively regulate SNS mainly through increasing ovule number by elongating placenta size [16].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of genes regulating fertility and seed set does not increase SNS because they do not enhance the ovule initiation and ovule number. Although GWAS analysis of ovule number identified NERD, which positively regulates ovule number and SNS, it still regulated ovule number through helping ovule development and fertility [60]. However, only a few genes were reported to positively regulate SNS mainly through increasing ovule number by elongating placenta size [16].…”
Section: Discussionmentioning
confidence: 99%
“…Protein sequence alignment analysis showed that PL1 shared high identities with the homologs identified, not only from primarily monocots and dicots but also from distantly related gymnosperms and cryptogams ( Figure 4G and Figure S9 and Table S4). Protein sequence alignment and phylogenetic analysis also showed that NEW ENHANCER of ROOT DWARFISM 1 (NERD1), an integrin-α N-terminal domain containing protein required for Arabidopsis reproductive development [56,57], is an orthologue of PL1 ( Figure 4G and Figure S9), suggesting a functional conservation between these two proteins. Overall, these results suggested that PL1 is a member of a highly conserved protein family in terrestrial plants.…”
Section: Pl1 Encodes a Conserved Integrin-α Fg-gap Repeat-containing mentioning
confidence: 97%
“…These chickpea gametophyte QTL had significant effects on sporophyte female fitness, not because the faster gametophytes are generally superior but because the gene is expressed in both pollen and seed pods. Similarly, a major regulator of ovule number, a sporophyte trait identified in a GWAS among A. thaliana accessions, exhibited significant overlap with male gametophyte development loci ( Yuan and Kessler, 2019 ). Evidence for pleiotropy between vegetative and reproductive tissue also appears outside of the seed plants.…”
Section: Does Gametophytic Selection Have Positive Negative or Neutmentioning
confidence: 99%